2013
DOI: 10.1371/journal.pone.0075033
|View full text |Cite
|
Sign up to set email alerts
|

Future Bloom and Blossom Frost Risk for Malus domestica Considering Climate Model and Impact Model Uncertainties

Abstract: The future bloom and risk of blossom frosts for Malus domestica were projected using regional climate realizations and phenological ( = impact) models. As climate impact projections are susceptible to uncertainties of climate and impact models and model concatenation, the significant horizon of the climate impact signal was analyzed by applying 7 impact models, including two new developments, on 13 climate realizations of the IPCC emission scenario A1B. Advancement of phenophases and a decrease in blossom fros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…'Brookfield Gala' model presented the best validation statistics (2.94 days). These RMSE values are similar to others in the literature for apple and other fruit trees blooming or budburst modeling studies and can be considered fairly precise for this kind of models (Luedeling, 2012): 4-6 days (Legave et al, 2013), 1.2-6.3 (Rea and Eccel, 2006) and 3.2-5.7 (Hoffmann and Rath, 2013) for apples, 4 days for peach trees (Miranda et al, 2013) and even wider ranges (4.7-29.8) for pear, cherry and kiwifruits (Cesaraccio et al, 2004).…”
Section: Endo-to Ecodormancy Shift Datesupporting
confidence: 87%
See 1 more Smart Citation
“…'Brookfield Gala' model presented the best validation statistics (2.94 days). These RMSE values are similar to others in the literature for apple and other fruit trees blooming or budburst modeling studies and can be considered fairly precise for this kind of models (Luedeling, 2012): 4-6 days (Legave et al, 2013), 1.2-6.3 (Rea and Eccel, 2006) and 3.2-5.7 (Hoffmann and Rath, 2013) for apples, 4 days for peach trees (Miranda et al, 2013) and even wider ranges (4.7-29.8) for pear, cherry and kiwifruits (Cesaraccio et al, 2004).…”
Section: Endo-to Ecodormancy Shift Datesupporting
confidence: 87%
“…Moreover, other studies have verified flowering advancements in the recent past for apple together with pear and other temperate fruits in South Africa (Grab and Craparo, 2011), Australia (Darbyshire et al, 2013), New Zealand (Clothier et al, 2012), Germany (Blanke and Kunz, 2009;Estrella et al, 2007), France (Guedon and Legave, 2008), and Central Europe (Menzel et al, 2006). Other studies using climate model projections showed also advancements of apple or other temperate fruits: apple in North Italy (Eccel et al, 2009) and Germany (Hoffmann and Rath, 2013), fruit trees in general in Central Europe (Trnka et al, 2011), grapevine in France for the end of the Century (García de Cortázar Atauri, 2006) and in Australia for mid century (Webb et al, 2007;Darbyshire et al, 2014). On the other hand, other authors found delays in the beginning of chill accumulation and fulfillment of CR, which should lead to later flowering (Luedeling et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Also, in this study the ensemble of climate models used was ENS-Spain02, especially developed for impact assessment . In spite of the low uncertainty detected, this one was slightly higher for future periods compared with the baseline due to inherent uncertainty of the climate models and was in agreement to Ferrise et al (2011) and Hoffmann and Rath (2013).…”
Section: Discussionsupporting
confidence: 51%
“…This is one of the largest uncertainty sources in climate change impact assessment as Iglesias et al (2010) for olive, Hoffmann and Rath (2013) for apple, Ruiz-Ramos and Mínguez (2010) and Asseng et al (2013) for wheat and maize described. However there are other relevant uncertainty sources not addressed here, as driving GCM, climate scenarios and others decisions related to climate .…”
Section: Discussionmentioning
confidence: 99%
“…In an apple phenology modeling study in Germany, Hoffmann and Rath (2013) found a decrease in frost risk for flowers in six out of seven model projections with the A1B emissions scenario despite an acceleration of first bloom date of 5.5 days C −1…”
Section: Frost and Freeze Damagementioning
confidence: 99%